Lipid biomarkers: lipidomics of the macrophage and plasma lipidomes - Dennis, Edward A. (Henry Stewart Talks, 2012)
The LIPID MAPS initiative, Relating LIPID MAPS to genomics, proteomics and metabolomics, Lipidomics analysis, Eicosanoid metabolism in macrophages, Lipidomics analysis of human plasma